Bases de dados no Brasil: um potencial inexplorado - da Cunha, Murilo Bastos (1989)
Apresenta a evolução do uso de bases de dados no exterior e no Brasil. Comenta e analisa os principais problemas que demandam soluções, tais como: custos, acesso a base de dados, treinamento dos usuários, marketing dos produtos e serviços, diferenças nas linguagens de busca, necessidade de maior cobertura de assuntos pelas bases de dados e o papel da iniciativa privada na emergente indústria de informação. Databases in Brazil: an unexplored potential Abstract The author comments the evolution of the use of databases in several countries, with emphasis on Brazilian utilization. The major problems and solutions related to databases, are discussed, such as: costs, access to databases, user training, marketing of products and services, differences among languages used in the searching process, need to enlarge the range of subjects covered by databases, and the role of the private sector in the emerging Brazilian information industry.